Dynamical credibility aware data forwarding mechanism for intermittently connected wireless networks - Da-peng WU; Hong-pei ZHANG; Ru-yan WANG; Qiao-shou LIU (Tongxin xuebao)
A novel dynamic credibility aware packet forwarding mechanism for intermittently connected wireless networks is proposed.According to the network state information obtained locally by a moving node,the malicious degrees and collaboration degrees of nodes can be obtained in a distributed manner.Meanwhile,based on the node connectivity,the credibility of a node is estimated,furthermore,the relay node can be selected reasonably.Results show that the proposed mechanism can effectively enhance the reliability of data transmission while reducing the network load rate significantly.Thus,the utilization of network resources is improved.